Unmet supportive care needs associated with quality of life for people with lung cancer: A systematic review of the evidence 2007–2020. (2nd November 2021) - Cochrane, Andy; Woods, Siobhan; Dunne, Simon; Gallagher, Pamela
Abstract: Introduction: The aim of this review was to systematically examine the evidence on the relationship between quality of life (QoL) and unmet supportive care needs in patients with lung cancer. Methods: Six databases were searched for studies published since 2007. Studies were included if they measured QoL using a standardised tool and examined its association with unmet supportive care needs in lung cancer patients. Results: Six studies involving 562 patients were included. Nearly two thirds of the patients had been diagnosed with advanced cancer (Stage III or IV), and the majority had been diagnosed for less than 2 years. There was a negative association between QoL and unmet needs using two different measures (Supportive Care Needs Survey[SCNS] and Cancer Survivors Unmet Needs Survey [CaSUN]). In two studies, the relationship was limited to physical and/or psychological domains. Conclusions: Unmet supportive care needs are associated with poorer QoL for people with lung cancer: The findings suggest that unmet physical and psychological needs may have the most impact on QoL and reflect the high symptom burden and psychological distress associated with lung cancer. Further work is needed to examine these relationships to identify the services and interventions that address the range of care needs across the disease trajectory.